The Historical Role Of Islamic Egypt - Ibrahim HUSSEIN Mahmoud (Cairo [ publisher not indentified ], 2020)
these papers deal with one topic , which is " The role of Islamic Egypt in its surroundings from the political , cultural and Intellectual points of view in Islamic periods"
Keywords: Prof. Dr. Mahmoud Ibrahim Hussein; Egypt -- History